Experimental Preeclampsia Causes Long-Lasting Hippocampal Vascular Dysfunction and Memory Impairment - Johnson, Abbie C.; Tremble, Sarah M.; Cipolla, Marilyn J. (Frontiers in Physiology, 2022)
Preeclampsia (PE) is a hypertensive disorder of pregnancy that is associated with memory impairment, cognitive decline and brain atrophy later in life in women at ages as young as early-to-mid 40s. PE increases the risk of vascular dementia three-fold, however, long-lasting effects of PE on the vasculature of vulnerable brain regions involved in memory and cognition, such as the hippocampus, remain unknown. Here, we used a rat model of experimental PE (ePE) induced by maintaining rats on a 2% cholesterol diet beginning on day 7 of gestation to investigate hippocampal function later in life. Hippocampal-dependent memory and hippocampal arteriole (HA) function were determined in Sprague Dawley rats five months after either a healthy pregnancy or ePE (n=8/group). Rats that had ePE were hypertensive and had impaired vasoreactivity of HAs to mediators involved in matching neuronal activity with local blood flow (i.e. neurovascular coupling). ePE rats also had impaired long-term memory, but not spatial memory. Thus, this model of ePE mimics some of the long-lasting cardiovascular and cognitive consequences that occur in women who previously had PE. These findings suggest endothelial and vascular smooth muscle dysfunction of HAs were present months after PE that could impair hippocampal neurovascular coupling. This represents a novel vascular mechanism by which PE causes early-onset dementia.